B(C6F5)3‐Catalyzed Hydroarylation of Terminal Alkynes with Phenols. Issue 16 (22nd July 2021) - Zhou, Jiaming; Huang, Jin; Lu, Changhui; Jiang, Huanfeng; Huang, Liangbin
Abstract: We developed a B(C6 F5 )3 catalyzed hydroarylation of terminal alkynes with various phenols at room temperature without adding any additives, leading to the synthesis of 2‐ gem ‐vinylphenols with good regio‐selectivity. Those transformations featured a broad substrate scope with moderate yields. Mechanism studies indicated that those transformations proceeded through the activation of phenol by B(C6 F5 )3 with subsequent protonation of alkyne/Friedel‐Crafts‐type reaction. Abstract :